Prediction of tensile and fracture properties of cracked carbon steel wires using finite element simulation - Adewole, Kazeem K.; Bull, Steve J. (Journal of Civil Engineering and Management, 2014)
Steel wires are used as a bridge construction material and as pre-stressing strands or tendons in pre-stressed structural units among other applications in civil engineering. To date, the estimation of the load carrying capacity of a cracked wire has been based on purely experimental classical fracture mechanics work conducted with non-standardised classical fracture mechanics specimens as standard test specimens could not be manufactured from the wire owing to their size. In this work, experimental mechanical tests and finite element simulation with the phenomenological shear fracture model has been conducted to investigate the effect of miniature cracks with dimensions less than or equal to 0.2 mm (which is the limit of the current non-destructive detection technology) on the tensile and fracture properties of flat carbon steel wire. The investigation revealed that the reduction in the displacement at fracture of the wire due to the presence of cracks shallower than 0.2 mm is significantly higher than the reduction in the fracture load of the wire. Consequently, the displacement at fracture and by extension the fracture strain capacity of the wire could serve as a more appropriate parameter to assess the quality and the structural integrity of cracked wires.